Detection of Viruses in Dentin Caries and Necrotic Pulp Caries Using ELISA Technique in Mosul, Iraq - Enas Yaseen Shehab; Anmar A. AlTaie; Basima A. Abdullah (Medical Journal of Babylon)
Background: Dental caries is a multifactorial disease that can affect human teeth, and viruses play a hidden role in forming caries cavities and dental plaque. Objectives: This study attempted to assess the detection of the role of some viruses such as Epstein-Barr virus (EBV), cytomegalovirus (CMV), herpes simplex virus type1 (HSV-1), and human papillomavirus (HPV) using the ELISA technique to detect the presence of viral antigens from three samples (dentine caries, necrotic pulp, and saliva) and to assess the relation between the presence of viruses and gender and age. Materials and Methods: From March 2022 to October 2022, samples were collected from 90 patients which were divided into three age groups, such as >20 years, 21–40 years, and ˂41 years, at the Dental Teaching Hospital of the University of Mosul. These patients represented both genders (45 men and 45 women). Results: The results indicated that the prevalence of HSV-1 was 66.6%, CMV was 68.8%, EBV was 86.6%, and HPV was 16.0% out of 90. The percentages of these viruses HSV-1, CMV, and EBV were higher in females than in males at 60.2%, 58.1%, and 43.4%, respectively, especially in the age group 21–40 years, with dominant of HSV-1 at 50%. Many studies focus on the role of bacteria in different types of dental caries, while the hidden role of viruses is excluded. Viruses play an important role in forming dental biofilm, and failed therapy may be due to viral infection. Conclusion: This study concludes that viruses in this study were detected in higher numbers in dentine caries, necrotic pulp, and saliva by ELISA technique, except human papillomavirus 16, which did not give any result.